Scaredy-cat, Splat! - Scotton, Rob. (New York : Harper, 2010)
Splat the cat accidently succeeds in being the scariest cat in the class for Halloween.
Publisher's Weekly
Publisher's Weekly, August 2010
2.1
K-3.
K-3
Keywords: Cats -- Juvenile fiction; Costume -- Juvenile fiction; Halloween -- Juvenile fiction; Cats -- Fiction; Costume -- Fiction; Halloween -- Fiction; Cats -- Fiction; Costume -- Fiction; Halloween -- Fiction; Picture books for children